Giant fetus in fetu in a female 'child with fever: A case report - Hanggoro Tri Rinonce Pieri Kumaladewi, Siti Iqbalwati Rochadi, Mei Neni Sitaresmi, Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Fetus in fetu is a form of monozygotic diamniotic twin pregnancy where the parasitic twin installs and grows in the body of its partner. It is a rare condition, with a reported incidence of 1 in 500.000 live births. The majority of these cases occur in children younger than 18 months with the chief complaint of an intraabdominal mass, and have a 2:1 male predominance. The size and weight of the fetus vary, from 4 cm to 24.5 cm and from 1.2 g to 1.8 kg. Whether this entity represents a highly differentiated teratoma versus a parasitic twin remains controversial. The objective of this paper was to report a rare condition of giant fetus in fetu in female child with fever, especially to emphasize the importance of proper examination. Although fetus in fetu is very rare, it should remembered as a possibility in an intraabdominal. In some cases further detailed examinations should be done to confirm the diagnosis. A rare case of giant fetus in fetu in a 20th month female patient with fever was reported. Intrabdominal mass was found as the first sign related to fetus in fetu but was neglected by the parents. USG, plain abdominal photo and CT-scan had revealed the diagnosis preoperatively. Proper examination of the fetus in fetu was done including grossly by doing extensive dissection, and detailed histological tissue examination from several sites to make diagnosis completely. Key words: giant fetus in fetu - fetiform teratoma - congenital abnormality - retroperitoneal, fever